The relation of ApoE and COMT gene–gene interactions to cognitive and motor function in community-dwelling older adults: a pilot study - Pizzonia, Kendra L.; Suhr, Julie A.; Clark, Leatha A.; Clark, Brian C. (Frontiers in Aging Neuroscience, 2023)
Introduction: Certain genes increase the risk of age-related neurological dysfunction and/or disease. For instance, ApoE is a well-known gene carrying risk for Alzheimer's disease, while COMT has been associated with age-related reductions in motor function. There is growing interest in the interrelationship between age-related changes in cognitive and motor function, and examining gene-gene interactions in this context. In this pilot study we examined the relations of the ApoE and COMT genes and their interaction to both cognitive and motor performance in community-dwelling older adults.We leveraged an archived dataset from a prior study on age-related muscle weakness in community-dwelling older adults. Sample size was between 72 and 82 individuals based on missing data. We examined the relationship of ApoE (Ɛ4 presence/absence), rs4680 SNP on the COMT gene (Val/Met, Val/Val, Met/Met), and sex on 1) overall cognitive functioning and specific cognitive domains known to decline in aging (processing speed, immediate and delayed memory, semantic and phonemic fluency, and executive functioning), and 2) indices of motor function (four square step test, short physical performance battery, grip strength/forearm lean mass, and purdue pegboard test).Results: Homozygous COMT genotypes were associated with worse global cognitive performance, immediate memory, and semantic fluency, but only for older adults with at least one ApoE Ɛ4 allele. There were main effects for COMT for delayed memory and a main effect for both COMT and ApoE for coding and phonemic fluency. Women scored higher than men in overall cognition, immediate and delayed memory, and semantic fluency. There were no main effects or gene interactions for a measure of executive functioning (trial making test part B) or any of the measures of motor function.Discussion: COMT, ApoE, and their interaction influence cognitive performance, but not motor functioning, in community dwelling older adults. Our work supports prior literature concluding that a heterozygous COMT genotype may be beneficial to sustain healthy cognitive functioning with advancing age for those who have a higher ApoE genetic risk status (at least one Ɛ4 allele). Future research should investigate interactions between COMT and ApoE in larger samples with comprehensive assessment of cognition and motor functioning.